2023
DOI: 10.3390/plants12244131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biochar Applied in Either Rice or Wheat Seasons on the Production and Quality of Wheat and Nutrient Status in Paddy Profiles

Zirui Chen,
Jiale Liu,
Haijun Sun
et al.

Abstract: In a rice–wheat rotation system, biochar (BC) applied in different crop seasons undergoes contrast property changes in the soil. However, it is unclear how aged BC affects the production and quality of wheat and the nutrent status in a soil profile. In the present soil column experiment, the effects of no nitrogen (N) fertilizer and BC addition (control), N fertilizer (N420) and BC (5 t ha−1) applied at rice [N420 + BC(R)], or wheat [N420 + BC(W)] seasons at a same rate of N fertilizer (420 kg ha−1 yr−1) on yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In addition, a meta-analysis of 103 publications found that pot experiments following the addition of biochar to the soil had the greatest effect on yield, which was greater in acidic soils (pH 5) than in field trials in neutral soils [ 135 ]. Likewise, a meta-analysis of 114 publications showed that the addition of biochar to soil significantly increased crop yields (about 20%) [ 19 ]. Overall, the meta-analysis studies suggest that biochar is a viable technology for yield enhancement in acidic and nutrient-poor soils.…”
Section: Biochar Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a meta-analysis of 103 publications found that pot experiments following the addition of biochar to the soil had the greatest effect on yield, which was greater in acidic soils (pH 5) than in field trials in neutral soils [ 135 ]. Likewise, a meta-analysis of 114 publications showed that the addition of biochar to soil significantly increased crop yields (about 20%) [ 19 ]. Overall, the meta-analysis studies suggest that biochar is a viable technology for yield enhancement in acidic and nutrient-poor soils.…”
Section: Biochar Impactsmentioning
confidence: 99%
“…Depending on location, deployment is not expected to have the same impact on soil fertility and carbon stability. Numerous studies, even laboratory studies, have shown the beneficial effect of using biochar and organic amendments on yields [ 17 , 18 , 19 , 20 ]. Several studies conducted in temperate regions showed no negative effects of biochar on the yield of various crops [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the leaf-based biochar had a higher nitrogen concentration. This finding suggests that the leaf-derived biochar has greater potential to raise the soil's total N content and improve plant uptake of N, both of which can increase the yields of crops such as wheat, rice, and grains [79][80][81].…”
Section: Discussionmentioning
confidence: 98%
“…Other studies of manure and BC in different forage species and soils reported a neutral effect on C. dactylon performance [ 28 ] and a positive effect on crops like radish [ 29 ] and cotton [ 4 ]. Several studies looking at soil parameters reported a wide range of contradicting BC effects [ 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%